Racial Misclassification of American Indian and Alaska Native People in the Electronic Medical Record: An Unexpected Hurdle in a Retrospective Medical Record Cohort Study - Ann Marie Rusk; Alanna M Chamberlain; Jamie Felzer; Yvonne Bui; Christi A Patten; Christopher C Destephano; Matthew A Rank; Roberto P Benzo; Cassie C Kennedy (Journal of Medical Internet Research)
AbstractElectronic health record data represent a rich data source; however, data accuracy must be considered prior to reporting health outcomes among American Indian and Alaska Native people. Using a hybrid approach to harmonizing data from multiple sources represents a valid method of assessing data integrity in this population.